Development of Audio-Visual Health Education Media on Chemotherapy for Parents in Caring for Children with Acute Lymphoblastic Leukemia at Darussalam 3 Pediatric Unit, Al-Islam Hospital Bandung - Siti Maelah; Rika Nurhasanah; Dyna Apriani; Iin Inayah; Nunung Nurjanah (Universitas Pahlawan Tuanku Tambusai, 2025)
Chemotherapy is considered the most effective treatment for children with Acute Lymphoblastic Leukemia (ALL) because it targets cancer cells that may have metastasized to other tissues. However, children undergoing chemotherapy experience both physical and psychological side effects, which also affect their parents. These impacts include changes in parental roles and responsibilities, limited knowledge about the disease, and the need for information to support independent care at home. This study aimed to develop audio-visual educational media on chemotherapy for parents of children with ALL based on their informational needs. A descriptive qualitative design with a Research and Development (R&D) approach was employed. Data were collected through in-depth interviews with seven parents, followed by the stages of initial planning, product development, and expert validation. Five major themes emerged: perceptions of chemotherapy, indications, side effects, management strategies, and educational media preferences. Expert validation by material and media specialists resulted in a feasibility score of 94.3%, categorized as highly appropriate. The study concludes that audio-visual educational media is feasible and effective as a health education tool to support parents in caring for their children during chemotherapy.